ANALYSIS OF LEADERSHIP AND MANAGEMENT GOVERNANCE IN THE ACCREDITATION POLICY OF MEDAN CITY AIR FORCE HOSPITAL - Lisa Yunita Marnas; Ermi Girsang; Sri Lestari Ramadhani Nasution (RADJA PUBLIKA, 2026)
Hospital management, leadership, and governance have an important role in ensuring the successful implementation of hospital accreditation policies. This study aims to analyze the influence of leadership and management governance on the implementation of accreditation policies at the Medan City Air Force Hospital. This study uses a mixed-methods approach with a sequential explanatory design, in which quantitative research is conducted first, followed by qualitative analysis to deepen the research findings. The quantitative sample comprised 80 health workers and managerial staff, selected using the total sampling technique. At the same time, qualitative data were obtained through purposive sampling involving five key informants: the hospital head, the hospital secretary, and the head of the installation. Data were collected through structured questionnaires with a Likert scale, in-depth interviews, observations, and document review. Quantitative data were analyzed using descriptive statistics and multiple linear regression, while qualitative data were analyzed using thematic analysis. The results showed that leadership had a significant effect on the implementation of hospital accreditation policies (β = 0.228; p < 0.05). Management governance also exerted a significant influence on the implementation of accreditation policies (β = 0.716; p < 0.05). These findings show that effective leadership and good management governance are important factors in strengthening the hospital's quality management system and ensuring the sustainability of accreditation implementation.